The Community Settlement Patterns Consistent with the Existence of the Cultural Heritages in Pathumthani Province: a Case Study of Rangsit City Municipality, Bueng Yitho Municipality and Thaklong Municipality - Khamwachirapithak, Putpunnin; Khamwachirapithak, Manunya (Asian Creative Architecture, Art and Design, 2020)
Pathumthani is an area with cultural diversities. Originally, there were settlements on riversides considered as a long history. The settlements were dispersed over other areas according to urban expansions. Regarding the mentioned changes, the original communities disappear, and the cultural heritages reflecting history are perishing. The purposes of this article are 1) to study the community expansion and settlement patterns, 2) to study the factors of the settlements, 3) to study the cultural heritages in the areas and the existence and 4) to present the settlement patterns consistent with the existence of the cultural heritages. The research instruments include surveys of land uses, transportations and locally cultural heritages as well as the in-depth interviews including the Head of the Community Development Department of Thaklong Municipality, the Director of the Welfare and Society Division of Rangsit City Municipality, the Mayor of Mueang Bueng Yitho Municipality and Pathum Thani Provincial Culture. The interview topics covered about the cultural heritages and existence, guidelines to promote inheriting the culture heritages, as well as problems and limitations of the cultural heritages. It was found that most of the expansions and settlement patterns were liner along the transportation routes by land and water, particularly in Klong Rangsit Prayoonsak Canal, where is an importantly and locally cultural heritage. There were the groups of the settlements with the religious centers such as mosques, Wat Khian Khet and Wat Moon Jindaram. There were also the expansions along the communities’ economic centers and educational institutes. Transportations, infrastructures and environmental influences were factors of changes of the settlement patterns and the lost values of cultural heritages. To conserve the values, it is suggested to have settlements and land uses along the Canal, to form groups in the economic centers and educational institutes and to promote the sub centers into settlements at the community level since the density is low.